The Role of Sentinel Node Biopsy in the Era of Adjuvant Therapy for Melanoma - Gabriella Brancaccio; Giulia Briatico; Camila Scharf; Giuseppe Colella; Giovanni Docimo; Ludovico Docimo; Mario Faenza; Francesco Iovino; Salvatore Tolone; Stefania Napolitano; Teresa Troiani; Andrea Ronchi; et al. (Mattioli1885, 2024)
Sentinel lymph node biopsy (SLNB) is a surgical procedure aimed to detect nodal metastases in patients with clinically occult disease. Since the advent of new systemic therapies, its role in melanoma has been extensively debated over the last years. In this article, three possible scenarios are discussed, considering the SLNB impact on the management of melanoma patients. First, pT1b and pT2a patients with negative SLNB (stages IA and IB) and those with positive SLNB (stage IIIA) would all not benefit from adjuvant treatment. Therefore, SLNB might be avoided in these categories of patients. Second, in IIB and IIC, melanoma patients are already candidates for adjuvant treatment; therefore, SLNB in patients with T3b, T4a, or T4b melanoma would not change treatment decisions. On the other end of the spectrum, patients with pT2b and pT3a melanomas (clinical stage IIA) represent the only two groups whose management would be significantly affected by the SLNB status, being adjuvant therapy only indicated for SLN-positive patients. Further studies are needed to investigate which melanoma patient deserves SLNB.